Food Marketing Targeted Towards Youth and Adolescence: Fast Food Preference in Urban India - Desai, Rahul (2013)
The main focus of this study is on children’s preferences for fast food in urban India. In the process of examining these preferences, the study also aims to determine the fast food outlet mostly preferred by kids and identify the drivers, motives and reasons for their popularity. Through this study, we also seek to identify the most popular meal among children and whether variables such as the background of the child, price, convenience, nature of product, and customer service play an important role in the decision-making process. The study also examines the influence of advertising on children’s fast food preference.